PENGARUH PEMBELAJARAN DARING TERHADAP MINAT BELAJAR FISIKA PESERTA DIDIK - Reski Idamayanti; Yusdarina Yusdarina; Irma Sakti; Nurhikmah Hasan (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
The purpose of the research was to determine whether there was an effect of online learning on the increase or decrease in students' interest in learning. The method used is a quantitative research method. The population in this research all students of class X at SMK Muhammadiyah Bungoro for the academic year 2021/2022. The sample in this research was determined by random sampling technique. In this random technique, class randomization will be used with the assumption that all populations are homogeneous. The sample in this research amounted to 30 people. In this research, the independent variable is online learning and the dependent variable is interest in learning. The instrument used in this research is a learning interest questionnaire. In the data analysis technique, this research uses the product moment correlation technique and simple linear regression with SPSS 16 for Window. Based on the results of the study, it can be concluded that there is an effect of online learning on interest in learning by showing significant results of 66.2%.